Penerapan Metode ARAS dalam Rekomendasi Handphone Terbaik untuk Youtuber Pemula dengan Pembobotan ROC - Abdullah, Mohammad Aldinugroho; Aldisa, Rima Tamara (BEES: Bulletin of Electrical and Electronics Engineering, 2023)
Mobile phones have evolved into versatile devices that can be used for a variety of purposes, including sending and receiving multimedia messages, surfing the internet, taking photos and videos, playing music, playing games, and running various applications. Mobile is not only a communication tool, but also a multimedia and productivity tool that is very important in everyday life, like a novice YouTuber who can use a cellphone to create his YouTube content. Beginner YouTubers refer to individuals who are just starting their journey in creating and uploading videos on YouTube. When creating video content, a novice YouTuber can use a cellphone, but when choosing a cellphone for creating content, a YouTuber must really choose. Because there are many choices of cellphones available now, it makes a novice YouTuber confused in determining the best cellphone to use. In choosing a cellphone for a novice YouTuber, there are several things to consider, namely Front Camera Resolution, Rear Camera Resolution, RAM, Internal Memory, Battery Capacity and Price. Then we need this information system which is also called a Decision Support System (DSS). SPK is a system that can help companies or organizations to make decisions on a problem they face. In this study, we applied the Additive Ratio Assessment (ARAS) method and ROC weighting, which is a method for making decisions and scoring criteria for obtaining the best cellphone recommendations for novice YouTubers, namely Infinix Zero 20 with a score of 0.92711 as an alternative that gets the highest score.